Density dependence of solar emission lines of oxygen-like ions - Raju P.K.; Dwivedi B.N. (My University, 2025)
Assuming steady state conditions, the occupation of 9 levels of oxygen-like ions: Ne iii, Mg v, Si vii, S ix, and Ar xi have been computed as a function of electron density and temperature. The following physical processes have been considered: collisional excitations and spontaneous radiative de-excitations for permitted and intercombination transitions; collisional excitations and de-excitations, photo-excitations and spontaneous radiative transitions among the five levels of the ground term. This study indicates that line intensity ratios for oxygen-like ions can be used as a diagnostic in the determination of these two parameters of the solar plasma. © 1978 D. Reidel Publishing Company.